Visual book design on Ibu Ruswo as a historical archive of Yogyakarta’s female hero: Perancangan buku visual kisah pejuang perempuan Ibu Ruswo sebagai media arsip sejarah tokoh dari Yogyakarta - Yuwono, Budi; Robbiya, Maiya Arsya (Universitas Negeri Yogyakarta, 2025)
Ibu Ruswo, a prominent female figure in Yogyakarta, played a significant role in the struggle and organisation of women during the war. Her name has now been immortalised as the name of a street. Her story is presented in a visual book, utilising the Pre-factum and Practice-Led Research methods, with data collected through interviews, observations, and literature reviews. The book's design is based on Visual Communication theory, encompassing design style, colour, layout, and typography. This book is intended for junior high and senior high school students in Yogyakarta to foster appreciation for women's struggles and increase interest in historical literacy. _______________________________________________________________________________ Ibu Ruswo, tokoh perempuan Yogyakarta, berperan besar dalam perjuangan dan organisasi perempuan pada masa peperangan. Namanya kini diabadikan sebagai nama jalan. Kisahnya diwujudkan dalam buku visual menggunakan metode Pre-factum dan Practice-Led Research, dengan pengumpulan data melalui wawancara, observasi, dan studi pustaka. Desain buku mengacu pada teori Komunikasi Visual, mencakup gaya desain, warna, tata letak, dan tipografi. Buku ini ditujukan untuk siswa SMP dan SMA di Yogyakarta guna menumbuhkan apresiasi terhadap perjuangan perempuan dan meningkatkan minat literasi sejarah.